Minimally invasive surgical treatment of minimally displaced acetabular fractures does not improve pain, mobility or quality of life compared to conservative treatment: a matched-pair analysis of 50 patients - Swartman, Benedict; Vetter, Sven Y.; Beisemann, Nils; Schnetzke, Marc; Keil, Holger; Grützner, Paul Alfred; Franke, Jochen (Journal of orthopaedic surgery and research, 2020)
Currently available procedures for the treatment of minimally displaced acetabular fractures include conservative treatment and minimally invasive percutaneous screw fixation. Screw fixation of acetabular fractures allows patients’ early full-weight bearing due to improved biomechanic stability. Can the range of motion, pain and mobility and quality of life in patients with acetabular fractures be improved by minimally invasive screw fixation, compared to conservative treatment in the long term?